The Emergence of Primary Anoetic Consciousness in Episodic Memory - Vandekerckhove, Marie; Bulnes, Luis Carlo; Panksepp, Jaak (Frontiers in Behavioral Neuroscience, 2014)
Based on an interdisciplinary perspective, we discuss how primary-process, anoetic forms of consciousness emerge into higher forms of awareness such as knowledge-based episodic knowing and self-aware forms of higher-order consciousness like autonoetic awareness. Anoetic consciousness is defined as the rudimentary state of affective, homeostatic, and sensory-perceptual mental experiences. It can be considered as the autonomic flow of primary-process phenomenal experiences that reflects a fundamental form of first-person “self-experience,” a vastly underestimated primary form of phenomenal consciousness. We argue that this anoetic form of evolutionarily refined consciousness constitutes a critical antecedent that is foundational for all forms of knowledge acquisition via learning and memory, giving rise to a knowledge-based, or noetic, consciousness as well as higher forms of “awareness” or “knowing consciousness” that permits “time-travel” in the brain-mind. We summarize the conceptual advantages of such a multi-tiered neuroevolutionary approach to psychological issues, namely from genetically controlled primary (affective) and secondary (learning and memory), to higher tertiary (developmentally emergent) brain-mind processes, along with suggestions about how affective experiences become more cognitive and object-oriented, allowing the developmental creation of more subtle higher mental processes such as episodic memory which allows the possibility of autonoetic consciousness, namely looking forward and backward at one’s life and its possibilities within the “mind’s eye.”